2002
DOI: 10.17221/6107-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Achievements and prospects of wheat breeding for disease resistance

Abstract: Achievements and prospects of wheat breeding for disease resistance in the world and in the Czech Republic are reviewed. Attention is paid to rusts, powdery mildew, leaf blotch, glume blotch, tan spot, fusarium head blight, common and dwarf bunt, eyespot, barley yellow dwarf virus on wheat and wheat dwarf virus. Genes for resistance to rusts and powdery mildew in the cultivars registered in the Czech Republic are listed. Promising resistance genes and sources of resistance to the above mentioned diseases are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The immune response on these cultivars could be as a result of hypersensitive responses; resistance often breaks down due to the development of new races of the pathogen. A suitable breeding strategy like the use of inter-specific and remote crosses or even the direct transfer of these resistances through backcrosses could be used to improve the adopted but highly susceptible wheat varieties being grown in Ethiopia (Bartos et al, 2002). On the other hand, the susceptible check, Morocco, displayed the highest disease severities of 60 and 70% with completely susceptible (S) responses during 2013 and 2014 cropping seasons, respectively, indicating that an acceptable epidemic pressure was established over the seasons for field experiments.…”
Section: Final Rust Severitymentioning
confidence: 99%
“…The immune response on these cultivars could be as a result of hypersensitive responses; resistance often breaks down due to the development of new races of the pathogen. A suitable breeding strategy like the use of inter-specific and remote crosses or even the direct transfer of these resistances through backcrosses could be used to improve the adopted but highly susceptible wheat varieties being grown in Ethiopia (Bartos et al, 2002). On the other hand, the susceptible check, Morocco, displayed the highest disease severities of 60 and 70% with completely susceptible (S) responses during 2013 and 2014 cropping seasons, respectively, indicating that an acceptable epidemic pressure was established over the seasons for field experiments.…”
Section: Final Rust Severitymentioning
confidence: 99%
“…Šíp et al () reported that the level of resistance to powdery mildew in presently grown Czech wheat cultivars was mostly not satisfactory and, therefore, an increase in the resistance level by breeding using local races becomes highly desirable. Partial or field resistance to such a variable pathogen as powdery mildew is undoubtedly of great importance (Bartoš et al, ) and it was observed in most of the tested Aegilops accessions. The most resistant Aegilops species to all tested diseases over years appeared to be Ae.…”
Section: Resultsmentioning
confidence: 99%
“…The trace reaction noted could be associated with hypersensitivity whereby fungal infection signals a defense mechanism leading to cell collapse which restricts further disease spread (Rubiales and Nicks, 2000). An appropriate crop improvement strategy like the use of inter specific and remote crosses or even the direct transfer of these resistance through backcrosses could be adopted to improve the adapted but highly susceptible wheat varieties being grown widely in Kenya (Bartos et al, 2002). The genotypes which displayed resistant to moderately resistant responses are of great importance to achieving effective breeding for durable resistance to stem rust.…”
Section: Discussionmentioning
confidence: 99%